2008
DOI: 10.1002/lary.20018
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a laryngeal dissection module for phonomicrosurgical training

Abstract: The laryngeal dissection module was validated as a surgical trainer. It was able to differentiate expert versus novice performance, and it improved novice performance through training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 13 publications
(14 reference statements)
2
67
0
Order By: Relevance
“…As Contag et al noted, ''Mastery of phonomicrosurgery is both challenging to achieve and difficult for the mentoring surgeon to teach while maintaining control of the operation.'' 13 Unlike a neck dissection and other open surgical procedures, the teaching surgeon cannot easily guide a trainee's hand during microscopic laryngeal surgery because of difficulties viewing the same field under binocular vision. The need for a formalized method of providing laryngeal education is further reinforced as laryngeal surgery is rapidly changing with new procedures and technologies constantly being introduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Contag et al noted, ''Mastery of phonomicrosurgery is both challenging to achieve and difficult for the mentoring surgeon to teach while maintaining control of the operation.'' 13 Unlike a neck dissection and other open surgical procedures, the teaching surgeon cannot easily guide a trainee's hand during microscopic laryngeal surgery because of difficulties viewing the same field under binocular vision. The need for a formalized method of providing laryngeal education is further reinforced as laryngeal surgery is rapidly changing with new procedures and technologies constantly being introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Contag et al used a plastic model larynx with sheets of paper modeling the vocal fold to teach microlaryngeal surgery, and while the device was well received, a concern of subjects was the need for a ''more 'lifelike' synthetic vocal fold.'' 13 Ex vivo training can come in many forms including human cadaver dissections, synthetic dissection models, live animal surgery, and virtual reality surgical simulators. 11,12 Virtual reality simulators were modeled after flight simulators in which aviators spend many hours practicing ''takeoffs and landings before they ever set foot in an airplane.''…”
Section: Discussionmentioning
confidence: 99%
“…Mohamed and Paczona described the use of cadaver larynx holders, and Amin et al used human cadaveric larynges for training vocal fold injection. Contag et al created a laryngeal dissection module using synthetic materials. Airborne contaminants generated during laser procedures may contain gaseous toxic compounds, bioaerosols, dead and live cellular material, and viruses.…”
Section: Discussionmentioning
confidence: 99%
“…There were fewer injuries of peripheral superficial tissues and surgical time was shorter compared to the group of residents that did no training on this specific model. 31 There are also virtual programs such as the larynx A few studies have shown that the ability to play musical instruments and electronic games is directly related with improved surgical performance, if approached correctly. Other authors have shown that practice in electronic games positively affects performance in videolaparoscopic surgery.…”
Section: Laryngologymentioning
confidence: 99%